2018
DOI: 10.4236/aer.2018.63003
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Peroxidation and Some Antioxidant Enzymes Evaluation in Apple Cider Vinegar (ACV) Treated Male and Female Wistar Rats Exposed to Chronic Restraint Stress

Abstract: This study was designed to assess the effect to apple cider vinegar (ACV) on oxidative stress biomarkers in male and female Wistar rats exposed to chronic restraint stress. Severe and persistent stress elevates reactive oxygen species (ROS) production by metabolic and physiological processes; causing cellular damage. Thirty (30) Adult Wistar rats of both sexes weighing about 150 -200 g were divided into 3 groups each consisting of a male and female subgroup and given the following treatments once a day for 21 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
3
1
0
Order By: Relevance
“…This finding agrees with the work of Forstermann and Munzel, 3 whose result revealed a significant increase in human low-density lipoprotein and cell membrane lipid on treatment with celecoxib. The result of this present study also agrees with the work of Abdulrauf, et al [4], whose result showed increased serum levels of oxidative stress biomarkers SOD, CAT and GSH-Px activities in the restraint stress rats, an indication of enhanced oxidative stress from the chronic stress induction.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…This finding agrees with the work of Forstermann and Munzel, 3 whose result revealed a significant increase in human low-density lipoprotein and cell membrane lipid on treatment with celecoxib. The result of this present study also agrees with the work of Abdulrauf, et al [4], whose result showed increased serum levels of oxidative stress biomarkers SOD, CAT and GSH-Px activities in the restraint stress rats, an indication of enhanced oxidative stress from the chronic stress induction.…”
Section: Discussionsupporting
confidence: 93%
“…Increased ROS production due to enhanced activity of ROS producing entities is an underlying cause of oxidative stress in tissues [15]. This is in line with the finding of Ahmad et al [18] and Abdulrauf et al [4], whose results showed a significant increase in MDA level in celecoxib treated rats and restraint stress rats respectively.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Induction of chronic restraining stress of 21 days led to increase in MDA and decrease in SOD concentrations. 15 Similar trend of decrease in SOD levels has been found when rats were subjected to chronic restraining stress of 21 days and increase in MDA concentrations were also estimated. 16 In chronic restraint stress rats with low serum NPY levels, showed raised behavioral sensitivity to normal anxiety, increased susceptibility to non-epileptic seizures and fear suppression.…”
Section: Variablessupporting
confidence: 67%
“…Apple cider vinegar is touted to have multiple cardiovascular benefits by exerting antiglycaemic, antioxidant, immunomodulatory, and anti-inflammatory properties along with aiding with weight loss, Although promising, there have been very few studies beyond in vitro or in vivo evidence (Abdulrauf et al, 2018;Ahmadifar et al, 2019;Budak et al, 2011;Halima et al, 2019;Tripathi et al, 2020). For example, the administration of apple cider vinegar during calorie-restricted dieting may improve weight loss thus supporting cardiovascular health (Khezri et al, 2018).…”
Section: Deriving Functional Beverages and Products From Beer And Cid...mentioning
confidence: 99%